1988
DOI: 10.1002/jbmr.5650030405
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion patterns and cytoskeleton of rabbit osteoclasts on bone slices and glass

Abstract: The ability of osteoclasts (OC) to migrate and resorb bone is thought to be dependent on cytoskeletal function and adhesion. Therefore, we investigated the cytoskeleton and the adhesion patterns of rabbit OC on glass and on devitalized bone slices, using specific antibodies to cytoskeletal elements and fluorescence and interference reflection microscopy. Microtubules (MT) were similar in OC on both substrata, and appeared in a pattern typical of that described for many cells. Multiple centriolar complexes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Radial MTs are oriented toward the cell periphery where podosomes form the belt (68,76), and growing MTs target podo- somes (29) and invadopodia (77). We found that a subset of growing MTs targets podosomes.…”
Section: Discussionmentioning
confidence: 70%
“…Radial MTs are oriented toward the cell periphery where podosomes form the belt (68,76), and growing MTs target podo- somes (29) and invadopodia (77). We found that a subset of growing MTs targets podosomes.…”
Section: Discussionmentioning
confidence: 70%
“…Osteoclasts recognize osteopontin on bone surfaces through vitronectin receptor α v β 3 , a member of the integrin families . Osteoclast recognition of their substrate of bone slices or synthesized surfaces, including glass and plastic surfaces of cell culture dishes, determines whether they behave as resorbing osteoclasts or non‐resorbing osteoclasts, respectively . Osteoclasts cultured on bone slices have been shown to have thick actin rings and TRAP localized in their upper levels and the cytoplasm around the nuclei, whereas osteoclasts cultured on glass coverslips have been shown to have thin actin rings and evenly distributed TRAP in the cytoplasm and periphery .…”
Section: Discussionmentioning
confidence: 99%
“…Podosomes on glass are well known to evolve from clusters to belts organized at the cell periphery during osteoclast differentiation (Teti et al 1991;Aubin 1992). On bone, dentin, or synthetic apatites, osteoclasts form resorption lacunae beneath the ruffled border region, where a dense continuous belt encloses the resorption lacunae (Turksen et al 1988;Lakkakorpi et al 1989;Vaananen and Horton 1995). This characteristic F-actin belt seems to correspond to the morphological accumulation of individual podosomes.…”
Section: Introductionmentioning
confidence: 96%